Perencanaan Arsitektur Enterprise pada Layanan Telekomunikasi Digital Telkomsel By.U menggunakan Zachman Framework - Hananto, April Lia; Guntur, Muhamad; Tukino, Tukino; Priyatna, Bayu (Ma'soem University, 2024)
One method for developing and managing a business is to apply the Zachman framework to the organization. This approach is also used by companies such as By.U for analysis and organization. The method of determining the use of By.U application company, a service provider, applying the Zachman framework, provides a practical area for businesses to evaluate the best course of action for creating an enterprise architecture related to significant issues with daily operations such as the insecurity of mobile phone numbers if they are written on manual paper at the pulse counter, this causes a large number of sms from unknown numbers. The results showed that the By.U application plays an important role in providing information about the choice of internet data package products. In addition, the implementation of the Zachman framework provides easy access for businesses to recognize benefits and drawbacks that arise based on the details of the services offered and provided by these organizations, making it easier for corporate representatives to make decisions within the organization.